Assessment of Motivation and Job Performance among Teachers -In Technical Schools in Akwa Ibom State - Silas, Edidiong Isonguyo; Ukpong, Paulinus Happy-Day (European Journal of Life Safety and Stability (2660-9630), 2022)
The center point of this paper was to assess the relationship between motivation and job performance of teachers in technical schools in Akwa Ibom State. Correlational research design was adopted for the study. The study was conducted in Akwa Ibom State. The population of the study comprised all teachers in technical schools. Simple random sampling technique was used 150 technical school teachers in Akwa Ibom State that constituted the sample size used for the study. The Instrument used in this study for data collection was a questionnaire titled: “Motivation and Teachers’ Job Performance Questionnaire (MTJPQ)”. Face and content validation of the instrument was carried out by an expert in test, measurement and evaluation to ensure that the instrument had the accuracy, appropriateness and completeness for the study under consideration. The reliability coefficient obtained was 0.80 and this was high enough to justify the use of the instrument. The researcher subjected the data generated for this study to appropriate statistical techniques such as Pearson Product Moment Correlation analysis. The test for significance was done at 0.05 alpha levels. It was established in this paper that teacher motivation plays an important role in the promotion of teaching and learning excellence. Generally, motivated teachers are more likely to motivate students to learn in the classroom, to ensure the implementation of educational reforms and feelings of satisfaction and fulfillment. Teacher motivation is very important because it improves the skills and knowledge of teachers because it directly influences the student's achievement. Based on the findings of the study, the study concluded that prompt payment of salaries, regular promotion, and training significantly influence job performance of technical school teachers in Akwa Ibom State. One of the recommendations made was that in order for teachers to perform well in their teaching activities, teachers need to undergo training in the form of in-service training with pay since teachers’ training is one of the most effective motivational variables which are the gateway to teachers’ positive performance.